Single-cell RNA-sequencing in novel preventative and therapeutic applications in breast cancer-related lymphedema - Suomi, Rebecca (My University, 2024)
Single-cell RNA-sequencing (scRNA-seq) is a form of new generation sequencing (NGS). It can be used to gather and analyse large datasets of single cells involving ribonucleic acid (RNA) -activity with precision and efficiency unattained by previous methods. scRNA-seq can be used to ascertain rare and detailed changes in a cell’s transcriptomic and proteomic activity in varying environments. In a clinical setting, it can be used to identify or guide new potential targeted therapies. Axillary lymph node dissection and biopsy, as well as radiative treatments and chemotherapy in conjunction with breast cancer surgery damage the axillary lymphatic system and heighten the risk of breast cancer-related lymphedema (BCRL) in the upper extremity. No curative or preventative treatment exists to date. Utilization of scRNA-seq could lead to new solutions regarding pharmacotherapeutic development in chronic secondary lymphedema. The aim of this literature review was to compile previous cellular and molecular information regarding lymphedema and present results gained about secondary lymphedema pathophysiology using scRNA-seq methods. scRNA-seq results suggest a pivotal role of CD4+-cells and TREM1-receptor overexpression in chronic inflammation, adipose hypertrophy, and fibrosis. A heightened expression of the LPL-gene and PPAR-gamma lead to adipose hypertrophy and the CLEC3B-gene in fibrotic progression. Dysregulated VEGF and PGFD signaling was central in inflammation, adipose hypertrophy, and fibrosis. Future studies would benefit from determining, whether molecular or cellular changes occur prior to discernible lymphedema. Surgical and conservative treatments have steadily secured a role in secondary lymphedema treatment, but scRNA-seq holds vast potential in developing novel targeted pharmacotherapeutic solutions for BCRL.

Yksisolu-RNA-sekvensointi (scRNA-seq) kuuluu uuden sukupolven sekvensointimenetelmiin (new generation sequencing, NGS). Sillä voidaan kerätä ja analysoida suuria datamääriä yksittäisten solujen ribonukleiinihappo (RNA) -aktiivisuudesta huomattavasti aiempia menetelmiä tarkemmin. Menetelmällä voidaan tunnistaa harvinaisia ja yksityiskohtaisia muutoksia yksittäisten solujen vasteesta esimerkiksi erilaisissa sairaustiloissa. Rintasyöpähoitojen yhteydessä tehtävät kainaloiden imusolmukepoistot sekä paikalliset säde- ja kemoterapiahoidot vaurioittavat imunestekiertoa sekä aiheuttavat usein imunesteturvotusta yläraajaan, eikä pitkäaikaiselle imunesteturvotukselle ole vielä saavutettu hyvää ennaltaehkäisevää tai parantavaa hoitovastetta. Hyödyntämällä yksisolu-RNA-sekvensointia imunesteturvotuksen tutkimisessa, voidaan löydöksiä mahdollisesti hyödyntää tulevaisuuden kohdennettujen hoitomuotojen kehittämisessä. Kirjallisuuskatsauksessa on koottu scRNA-seq tutkimuksia sekundaarisen imunesteturvotuksen patofysiologiasta. Tuloksissa muun muassa CD4+-solulinja sekä TREM1-reseptori omaavat tärkeän roolin tulehdusprosessin etenemisessä ja rasva- ja sidekudosmuodostuksessa. LPL-geeni ja PPAR-gamman lisääntynyttä ilmentymää on havaittu rasvakudoksen hypertrofian taustalla ja CLEC3B-geenin ilmentymää fibroosissa. VEGF ja PDGFD-viestintä olivat keskeisiä tulehdus- sekä rasva- ja sidekudosmuutosten osalta. Tulevaisuudessa olisi tärkeää selvittää, ilmeneekö keskeisiä merkkiaineita tai muita määritettäviä solu-, molekyyli- tai RNA-tason muutoksia jo ennen kliinisesti havaittavan imunesteturvotuksen kehittymistä. Kirurgiset ja lääkkeettömät hoitomuodot tulevat säilyttämään roolinsa, mutta yksisolu-RNA-sekvensoinnin avulla voidaan kohdentaa uusia hoitomuotoja lääkekehityksen osalta.
Keywords: scRNA-seq, single-cell RNA-sequencing, breast cancer-related lymphedema, BCRL